Interaction effects of multiple damage mechanisms in composite sandwich beams subject to time dependent loading - Massabò, R.; Cavicchi, A. (International journal of solids and structures, 2012)
Theoretical models are formulated to explain evolution and interaction of the damage mechanisms for multiple delamination of the face-sheet and core crushing in composite sandwich beams subjected to dynamically applied out-of-plane loading and continuously supported by rigid planes. The models are based on simplified one-dimensional formulations and describe the impacted face of the sandwich as a set of Timoshenko beams joined by cohesive interfaces and resting on a nonlinear Winkler foundation, which approximates the response of the core; the dimensionless formulation highlights the material/structure groups that control the mechanical response. The characteristic features of the problem and transitions in damage progression are explored on varying geometrical parameters and material properties and magnitude and duration of the applied load. For quasi-static loading and low velocity impact, core/face-sheet interactions generate energy barriers to the propagation of delaminations; the efficacy of the barriers in controlling damage in the face-sheets depends on the relative stiffnesses of face-sheet and core and on the foundation yielding strength. For dynamic loading conditions, significant dynamic effects arise in certain regimes and cause substantial changes in behavior: shielding of the crack tip stress fields provided by the foundation is reduced, especially after the load is removed when important delamination openings occur; core plasticity generally opposes this behavior and limits damage in the face-sheet.